Remarkably high fracture toughness of HfNbTaTiZr refractory high-entropy alloy. (1st October 2022) - Fan, X.J.; Qu, R.T.; Zhang, Z.F.
Highlights: The fracture behavior of the Hfnbtatizr refractory HEA was investigated. The HEA exhibits a remarkably high fracture toughness of K JIC  = 211 MPam 1/2 . Fully-ductile fracture mode with the formation of kink bands was observed. The excellent damage-tolerance plus high strengths in a wide temperature range endow this HEA a promising structural material. Abstract: High-entropy alloys (HEAs) with face-centered cubic (FCC) phase such as CoCrFeMnNi or CoCrNi generally exhibit ultra-high fracture toughness but relatively low strength. In contrast, body-centered cubic (BCC) HEAs often display higher strengths, but the few reports on fracture toughness measurement demonstrate low toughness values. Here we show that the BCC HfNbTaTiZr refractory HEA, which possesses a combination of high strength, good tensile ductility and excellent high-temperature properties, also exhibits a remarkably high fracture toughness. By using the "single specimen" compliance method for J -integral measurement according to the ASTM E1820–17 standard, its fracture toughness K JIC was experimentally determined to be 210 MPa m 1/2, which renders this HEA among the toughest metallic materials. The excellent damage tolerance makes the HEA promising for applications as high-temperature structural materials such as in aerospace field.